OPTIMIZING MSME PRODUCT AUTHENTICITY VERIFICATION IN DECENTRALIZED MARKETS USING BLOCKCHAIN - Adnan Zulkarnain; Mukhlis Amien (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
Blockchain technology offers a solution for ensuring product authenticity in decentralized digital marketplaces. However, Micro, Small, and Medium Enterprises (MSMEs) face barriers such as limited infrastructure, high costs, and data interoperability challenges. This study develops a hybrid blockchain-based application architecture tailored to MSME needs, integrating on-chain and off-chain storage. Critical security data, such as product hashes, is stored on-chain, while non-sensitive data, like product descriptions, is managed off-chain using a cloud-based MySQL database. This design reduces storage costs and computational load while maintaining data integrity. Ethereum smart contracts manage product registration and verification, linked to QR code-based authentication for end-users. A realistic simulation environment using server-based infrastructure and cloud databases evaluated system performance, including transaction throughput, latency, resource utilization, and scalability. The results show significant improvements compared to conventional centralized methods, achieving a transaction throughput of 391 TPS for 1 million transactions while maintaining low latency and resource efficiency. This research addresses a theoretical gap by optimizing blockchain for small-scale decentralized markets, tackling resource limitations and interoperability issues unique to MSMEs. Practically, it provides a scalable and cost-effective solution for product authenticity verification, enhancing consumer trust and reducing counterfeiting in MSME digital markets. While real-world testing remains a limitation, the findings underline the system’s potential to support sustainable MSME digital marketplaces and build consumer confidence.